Complete Convergence of Weighted Sums for Arrays of Rowwise $m$-Negatively Associated Random Variables (Communications in Mathematical Research, 2021)
In this paper, we discuss the complete convergence of weighted sums forarrays of rowwise $m$-negatively associated random variables. By applying momentinequality and truncation methods, the sufficient conditions of complete convergenceof weighted sums for arrays of rowwise $m$-negatively associated random variables areestablished. These results generalize and complement some known conclusions.
Keywords: complete convergence; negatively associated; $m$-negatively associated; weighted sum.